Pneumococcal carriage following PCV13 delivered as one primary and one booster dose (1 + 1) compared to two primary doses and a booster (2 + 1) in UK infants. Issue 19 (5th May 2023) - Goldblatt, David; Andrews, Nick J.; Sheppard, Carmen L.; Rose, Samuel; Aley, Parvinder K.; Roalfe, Lucy; Southern, Jo; Robinson, Hannah; Pearce, Emma; Plested, Emma; Johnson, Marina; Litt, David J.; et al.
Abstract: In January 2020 the UK changed from a 2 + 1 schedule for 13-valent pneumococcal conjugate vaccine (PCV13) to a 1 + 1 schedule (doses at 3 and 12 months) based on a randomized immunogenicity trial comparing the two schedules. Carriage prevalence measured at the time of booster and 6 months later in 191 of the 213 study infants was 57 % (109/191) and 60 % (114/190) respectively. There were eight episodes of vaccine-type (VT) or vaccine-related 6C carriage in the 2 + 1 and six in the 1 + 1 group; ≥4-fold rises in serotype-specific IgG in 71 children with paired post-booster and follow up blood samples at 21–33 months of age were found in 20 % (7/35) of the 2 + 1 and 15 % (6/41) of the 1 + 1 group. VTs identified in carriage and inferred from serology were similar comprising 3, 19A and 19F. Dropping a priming dose from the 2 + 1 PCV 13 schedule did not increase VT carriage in the study cohort. Ongoing population level carriage studies will be important to confirm this.